PELAKSANAAN KEWENANGAN BADAN NARKOTIKA NASIONAL PROVINSI RIAU DALAM MEMUTUS PENGEDARAN NARKOBA JARINGAN INTERNASIONAL DI PROVINSI RIAU TAHUN 2018-2019 - Wagi Astuti; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Narkoba stands for narcotics, psychotropic drugs and illegal drugs. Apart from "drugs", another term introduced in particular by the Ministry of Health of the Republic of Indonesia is Napza which stands for narcotics, psychotropic substances and addictive substances. Narcotics are needed by humans for treatment so that to meet the needs in the field of medicine and scientific studies, a continuous production of narcotics is needed for these sufferers. This is in line with the preamble to Law Number 35 of 2009 concerning Narcotics which explains that narcotics on the one hand are drugs or substances that are useful in the field of medicine or health services and the development of science and on the other hand can cause dependency which is very detrimental if misused or used without strict and careful control and supervision.The method used in this research is qualitative, the data sources used in this study include primary data and secondary data, the location of the study was conducted at the National Narcotics Agency of Riau Province. Research informants in this study were the Head of Section for the Eradication of the Narcotics Agency of Riau Province, Commission I DPRD of Riau Province. The theoretical concept used in this research is the theory of authority and the theory of the success of the implementation of bureaucratic tasks in comparing, taking corrective action. This study uses qualitative research methods, data collection techniques used are interviews, observation and documentation.From the research results, that the implementation of authority exercised by the National Narcotics Agency of Riau Province has not been effective. because there are still many cases of drug trafficking in international networks that occur, and Riau Province as a route where every year there is an increase in international illicit drug trafficking, especially from neighboring countries through unofficial ports. The factors inhibiting the implementation of the authority of the Riau Province National Narcotics Agency are the lack of personnel, the lack of supporting facilities in the field, the large number of unofficial ports that are used as places for transactions, and the lack of public awareness to report drug transactions.Keywords: Authority, Cut Circulation Drugs.